ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN SEKTOR PERDAGANGAN BESAR - Faisal Aji Syahputra; Eko Purwanto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to assess the effect of financial ratios on financial distress in large trading sub-sector companies on the IDX in 2018-2020. In this case, the researcher uses financial ratios which include liquidity, solvency, profitability, and activity. The projection of financial distress is the modified Altman Z-Scored formula. The sample was determined by purposive sampling. The number of samples is 26 companies. To test the hypothesis of this study using multiple linear regression. The results of the study show that the four ratios have a significant positive effect on financial distress. The value of Adjusted R2 is 0.650, so the four ratios can predict financial distress of 65%.